Assessing Trustworthiness of Personal Aides - Denise Clark Lewis PhD; Won Jee Cho MS (SAGE Publishing, 2011)
Background: Smaller family size has increased the need for assistance from personal aides. Respite care provided by personal aides reduces depressive symptoms and improves intergenerational relations and overall well-being of family members and patients. Yet, little is known about how family members evaluate personal aides prior to and during the employment period. Methods: Qualitative semistructured interviews were conducted face-to-face with 10 families providing home-based care. Family members' ages ranged from 43 to 70 years. Patients' ages ranged from 67 to 86 years. Interviews were audio-recorded and transcribed verbatim. Data were coded and themes were identified. Results: Family members emphasized the importance of personal aides. Other concerns included protection of their loved ones against risks from dishonest, unethical, or incompetent personal aides and unsafe, uncomfortable caregiving contexts. After family members hired a personal aide they presumed to be trustworthy, monitoring was a nearly endless task in seeking assurance that their initial assessment was accurate. Conclusions: Appropriate care, according to family members, went far beyond actions required to competently administer medicines, assist with activities of daily living, or maintain a watchful presence in the home. While positive experiences with personal aides added to the quality of life for both family members and patients when trustworthiness was established, quite the opposite was found when trust was violated. Personal relations, interpersonal communication skills, and affection between the aide and the patient were found to be much more important in determining trustworthiness than were standard caregiving skills.